Pengaruh Vitamin D3 Terhadap Glukosa Darah Tikus Wistar Yang Dipapar Asap Rokok - Lolita Putri Nanda Utami; Hetti Rusmini; Yessi Nurmalasari; Dessy Hermawan (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Cigarettes are the biggest health problem around the world. Nicotine in cigarettes has been proved insulin receptor resistance and can reduce insulin secretion in pancreatic β cells, which causes an increase in blood glucose levels. One of the efforts to reduce blood glucose levels is to consume vitamin D3. Vitamin D3 is a prohormone that plays a role in metabolic functions in cells and repair functions of cells. Purpose: to know the effect of vitamin D3 toward glucose blood level of male Rattus norvegicus Wistar exposed by cigarette smoke. Methods: This research conducted with pure experimental pre- and post-test with control group design. The samples used were 24 male rats. The sample divided into four groups, including K1, K2, K3, and P1. K1, which is not exposed by cigarette smoke and not given of vitamin D3. K2 is a group exposed by cigarette smoke but not given vitamin D3. K3 is a group that is not exposed by cigarette smoke but given vitamin D3 a dose of 0.2 µgr /head. P1 is a group exposed by cigarette smoke and given a vitamin D3 dose of 0.2 µgr /head. Results: Paired T-test showed increased blood glucose levels that are meaningful (p<0,05) In groups K2 (p=0,018) and P1 (p=0,035). One-way Anova showed there were differences in blood glucose levels that are meaningful between groups (p=0,001). Statistical analysis Post Hoc LSD showed significant differences in group K1 with K2 (p=0,004), group K1 with K3 (p=0,038), group K1 with P1 (p=0,038), group K2 with K3 (p=0,000), group K2 with P1 (p=0,004). Conclusion: Vitamin D3 can reduce fasting blood glucose levels of Rattus norvegicus exposed by cigarette smoke.